Pengaruh Pemberian Kredit dan Modal terhadap Pendapatan Pedagang Kecil - N, Nelfa; Zuraidah, Zuraidah; Sartika, Fani (Universitas muhammadiyah palembang, 2019)
Income is one important factor to measure the success of micro businesses. Increased capital also allows obtaining additional income for micro businesses. Koperasi Karya Indonesia Banda Aceh is one of the cooperatives consisting of micro entrepreneurs. This study aims 1) To determine the effect of giving capital and giving credit together to the income of small traders 2) To determine the effect of giving capital and giving credit partially to the income of small traders. The study uses a quantitative approach which is correlation research. There are three variables developed as a basis for assessment. There are 295 cooperative members as a population taken 62 as a sample. The data needed is primary data with questionnaire data collection methods. The analysis technique used is multiple linear regression. The results of the research prove that 1) There is an effect of giving capital and giving credit together to the income of small traders 2) There is an effect of giving capital and giving credit partially to the income of small traders